Competition in Higher Education: A Survey - Michael Kaganovich; Sinan Sarpca; Xuejuan Su (Center for Economic Studies and ifo Institute (CESifo), 2020)
The structure and functioning of the market of higher education in the United States possess distinctive if not puzzling features such as the wide spectrum of institutional arrangements and sources of funding, stark segmentation in levels of selectivity and instructional resources, and high variance in tuition pricing across and within institutions, including price discrimination based on merit and ability to pay. At the same time, many fundamental questions, including what defines the quality of higher education and explains its (growing) cost continue to be debated. The Chapter surveys theoretical analyses addressing this range of issues.
Keywords: I21; I22; I23; D40; J24; 330